Glossodynia And Its Associated Risk Factors In Patients with Geographic And/Or Fissured Tongue at Hawler Medical University: A Retro-Prospective Cross-Sectional Study - Rezao Omar Hasan; Sameeh Sdiq Omar; Jamal Qader Ahmed; Shahen Ali Ahmad (Erbil Dental Journal, 2025)
Background: Glossodynia is characterized by a painful sensation in the tongue, often accompanied by sleep disturbances, exhaustion, and psychological issues, including anxiety and depression. Glossodynia manifests with a typical oral symptom, such as a burning mouth sensation. Hence, it is important for oral healthcare practitioners to possess knowledge about this clinical condition.